THE USED OF GAMIFICATION ON STUDENTâS UNDERSTANDING ABOUT TRANSPORTATION MODE IN THE SUPPLY CHAIN - Hikmatullah
Nowadays, supply chain management (SCM) is being one of the important knowledge usable in business implementation. Supply chain management covers the planning and control of all manufacturing. The main problem in the design of a large supply chain for manufactured products is how the product is transported to the consumer from the manufacturing plant. Each company is aware of the importance of transport management for any supply chain. This topic is also important to be learned by students in a school of business and management. In learning supply chain management, students are expected to be able to understand the role of different transportation modes in a supply chain, identify relative strengths and disadvantages of various design choices in the transportation modes, and be able to choose a mode of transportation according to condition. In the early spring of 2020, most governments around the world have temporarily closed educational institutions to contain the spread of the COVID-19 pandemic. Due to the current condition, most universities around the world change their system from conventional to online learning (e-learning). This situation has positioned information technology to function as a viable innovative platform to create a creative way of learning. An alternative to a learning method that can be used in e-learning is gamification or game-based learning. The study aims to design an online game that can help students understand the topic of transportation in a supply chain and achieve the learning outcomes. The experiment is conducted to see the effect of the gamified method on learning outcomes. Data analysis shows that there is a significant improvement in score test, and there is a positive correlation of gamification method against learning outcomes achievement. But, the designed game is not better than asynchronous online learning. Additionally, the result of the study shows that challenge/skill balance and clear goals are the most important of game elements in developing gamification.